STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN DISIPLIN GURU - Luqmanul Hakim; Najmi Faza (AL-BAYAN INSTITUTE, 2025)
The low quality of human resources is one of the most basic problems that can hamper the educational process, which is one of the causes of the low quality of education in Indonesia, namely the low quality of teachers. Human resources are one of the factors that need to be considered in implementing teaching activities in the field of education, and teachers are the main carriers of the intellectual growth of the younger generation.The approach used is a qualitative approach. Qualitative research is a research rule that will produce descriptive data in the form of written or spoken words from parties directly involved in the author's research. Meanwhile, the type of research used is a case study, with the aim of obtaining a complete and in-depth description of an entity. Case studies produce data which is then analyzed to produce theories. The leadership strategy needed in schools is a leadership strategy that is able to push towards a better direction. Through good leadership strategies, a madrasa head can improve and increase teacher discipline in accordance with the goals, hopes, vision and mission carried out by the school. If the madrasah principal implements leadership strategies well and continuously in all teacher activities at school, a better work environment will be created in the future for teachers. Disciplinary problems are basic and general problems in the educational environment. At MI Miftahul Falah, common disciplinary problems usually occur in the form of teachers being late in coming to the madrasah in the morning or when lessons start in class. In responding to forms of violations committed by MI teacher Miftahul Falah, the head of the madrasah made efforts in the form of implementing rules and regulations containing rules and sanctions for teachers. The application of rules and regulations aims to instill an awareness of the value of discipline in teachers. Meanwhile, sanctions aim to provide a deterrent effect for teachers who violate the rules.